The bibliometric and content analyses for the concepts of trust and social media in recent scholarly journals = Pojęcia "zaufanie" i "media społeczne" w czasopismach naukowych w świetle analizy bibliograficznej i analizy zawartości - Dogan, Duygu (Zielona Góra: Lubuskie Towarzystwo Naukowe)
Trust has been a key concept in interpersonal and organizational communication literature in recent years. The use of new media technologies and social networking systems in corporate and marketing communication has brought about the need for studying trust and social media in various aspects.
Keywords: revitalization; participations; empowerment; practice; action research; zaufanie; media społecznościowe; studia nad komunikowaniem; analiza zawartości treści; zaufanie do mediów